Verticalização, microclima e o conforto térmico dos espaços abertos públicos: estudo de caso em João Pessoa–PB - Carvalho, Guilhardo Barros Moreira de (2023)
Urbanization and changes in land use pose significant challenges for urban planners due to city growth. Studies highlight the influence of human activities on temperature increase, which is directly related to land use and occupation characteristics. Microclimate research seeks adaptive approaches to meet social needs. Public spaces, particularly those with green areas, play an essential role in the social fabric by fostering interactions, improving air quality, reducing urban heat, conserving biodiversity, promoting physical activity, and providing recreational areas. This study analyzed the effects of verticalization in an area called "Três Ruas" located in João Pessoa, Paraíba. The effects of verticalization on microclimate dynamics and thermal comfort in open spaces and adjacent areas were investigated using the computational simulation tool ENVI-met. The results demonstrated that increased verticalization negatively impacted the Sky View Factor (SVF), indicating obstruction and influencing microclimate and thermal comfort. However, the presence of elements such as trees, empty spaces, or buildings contributed to attenuating this adverse effect. Thermal comfort indices such as Physiologically Equivalent Temperature (PET) and Universal Thermal Climate Index (UTCI) were analyzed in different scenarios and times. The results revealed variations throughout the day, with periods of moderate thermal discomfort, especially between 3 pm and 6 pm. Air humidity showed variations influenced by factors such as shading, solar radiation, and vegetated areas. Wind speed also revealed differences in the analyzed sectors, with significant correlations between wind speed and SVF. Mean radiant temperature (MRT) varied throughout the day. It was concluded that verticalization alone is not sufficient to control urban heat. The results provide urban planning, architecture, and public health inputs to create environments adapted to climatic conditions.